Bioinformatics and immunoinformatics to support COVID‐19 vaccine development. Issue 9 (23rd April 2021) - Ishack, Stephanie; Lipner, Shari R.
Abstract: Severe acute respiratory syndrome coronavirus 2 has infected over 109 000 000 people with 2 423 443 deaths as of February 17, 2021. Currently, there are no approved or consistently effective treatments, and conventional vaccines may take several years for development and testing. In silico methods of bioinformatics, vaccinogenomics, immunoinformatics, structural biology, and molecular simulations can be used for more rapid and precise vaccine design. This paper highlights two major immunoinformatics strategies that are used in designing novel and effective vaccines and therapeutics: reverse vaccinology and structural vaccinology.